Pendampingan Identifikasi Potensi Wisata Nagari Guguak Malalo dalam Menghidupkan Ekosistem Desa Wisata - Afrilian, Pepy; Rizal; Putri, Dianni Oktaria (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Facilitating the Identification of Tourism Potentials in Nagari Guguak Malalo to Revitalize the Village Tourism Ecosystem Nagari Guguak Malalo, Tanah Datar Regency, is a region abundant in natural resources, characterized by expansive hills and the scenic beauty of Lake Singkarak. Therefore, the mapping of tourism potentials serves as the foundation in the planning and development processes of tourism managed by the Community-Based Tourism Organization (POKDARWIS) and the local community. The mapping process encompasses several stages, including a forum group discussion that explores various tourism potentials through the lenses of natural, cultural, and artificial attractions. Subsequently, a mapping is conducted using a tourism potential matrix, emphasizing the strengths and weaknesses of feasible tourism activities. The matrix results are then reevaluated across multiple sectors, culminating in a Joint Decision. For short-term planning, this involves the execution of cultural events, which are also incorporated into the Tanah Datar Regency's event calendar. Additionally, there is the introduction of religious tourism packages. Looking towards the medium-term plan, efforts are directed at enhancing accessibility and infrastructure for nature-based tourism. Simultaneously, the development of water tourism is pursued by optimizing the available human resources ready to engage in the tourism industry within the framework of a tourism village concept.